2022
DOI: 10.1111/micc.12749
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of white matter lesions in hospitalized COVID‐19 patients: A meta‐analysis

Abstract: Objective Novel coronavirus disease 2019 (COVID‐19) has been found to be associated with encephalopathy and brain imaging abnormalities. The identification of incident white matter lesions, known to be associated with cerebral microcirculatory failure and cerebrovascular disease, in COVID‐19 patients is of clinical and scientific interest. We performed a meta‐analysis to investigate the incidence of white matter lesions (WMLs) in hospitalized COVID‐19 patients. Methods PubMed, EMBASE, and the Cochrane Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A recent review of several clinical case studies also highlighted spinal involvement of COVID-19 infections, providing valuable insights into the diagnoses and management of affected patients [ 150 ]. Similar findings were recently reported in previous systematic reviews [ 7 , 14 , 151 ]; however, most of these studies are limited by methodological heterogeneities including the inclusion of relatively small sample studies and cases ( n < 10 patients in brain studies) and irreproducible literature search strategies.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…A recent review of several clinical case studies also highlighted spinal involvement of COVID-19 infections, providing valuable insights into the diagnoses and management of affected patients [ 150 ]. Similar findings were recently reported in previous systematic reviews [ 7 , 14 , 151 ]; however, most of these studies are limited by methodological heterogeneities including the inclusion of relatively small sample studies and cases ( n < 10 patients in brain studies) and irreproducible literature search strategies.…”
Section: Introductionsupporting
confidence: 82%
“…While it was initially identified as predominantly a respiratory infection [ 2 ], COVID-19 is now widely considered a multisystemic disease, causing cardiovascular, renal, gastrointestinal, hepatic, haematological [ 3 ] and metabolic disorders [ 4 ]. Accumulating evidence has highlighted potential relationships and involvement of the central nervous system (CNS) in the invasion mechanism of the virus [ 5 , 6 ] as evidenced in large cohorts of patients displaying neurological manifestations [ 7 9 ]. For example, in a cohort of patients hospitalised with COVID-19 ( n = 214) in Wuhan, 36.4% presented with neurological symptoms, including dizziness, headache, impaired consciousness, and acute cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noticed that patients with less severe course and those who stayed in hospital for a shorter time had less severe white matter abnormalities [ 201 ]. In a meta-analysis that included studies with a total group of 362 COVID-19 patients, WM abnormalities were observed in 20% of hospitalized group [ 202 ]. Damage to WM may have a hypoxic-ischemic cause, therefore the most vulnerable are patients with severe course of COVID-19 and requiring active oxygen therapy [ 203 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brain imaging has gained increasing popularity among neuroscientists and clinicians, including academic radiologists, as a tool to study brain structure and function, as well as to aid diagnosis and prognosis and guide the treatment of brain diseases [ 1 , 2 , 3 ]. Even during COVID-19, brain imaging techniques such as magnetic resonance imaging (MRI) were used to detect brain abnormalities [ 4 ]. Researchers and bioethicists have been debating how to handle incidental findings (IFs) in brain imaging research studies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%